1939
DOI: 10.1017/s0022172400012031
|View full text |Cite
|
Sign up to set email alerts
|

Incubation at 44°C. as a test for faecalcoli

Abstract: 1. The use ofEsch. colialone as an index of faecal pollution for shellfish, and the correlation between the 44° C. MacConkey test and citrate tests are discussed.2. The mercury-toluene thermo-regulator used in these experiments, which gives a maximum variation of ± 0.1° C., is discussed briefly and illustrated.3. Experiments are described in which 522 colonies from polluted shellfish were isolated, inoculated into MacConkey's broth and incubated at temperatures of 37° C. and at successive 1° intervals from 41 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

1941
1941
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The concept of fecal indicator organisms for water was operationally defined in 1901, when the coliform group was defined as Gram-negative, non-spore-forming facultative, anaerobic bacilli that ferment lactose, with production of acid and gas within 48 h (50). Later it was found that organisms defined as such are not always related to fecal contamination, and by 1904, C. Eijkman included a higher incubation temperature of 44°C to improve the specificity of the indicator (15). These fecal coliforms, or thermotolerant coliforms, are considered to be specific to fecal pollution.…”
mentioning
confidence: 99%
“…The concept of fecal indicator organisms for water was operationally defined in 1901, when the coliform group was defined as Gram-negative, non-spore-forming facultative, anaerobic bacilli that ferment lactose, with production of acid and gas within 48 h (50). Later it was found that organisms defined as such are not always related to fecal contamination, and by 1904, C. Eijkman included a higher incubation temperature of 44°C to improve the specificity of the indicator (15). These fecal coliforms, or thermotolerant coliforms, are considered to be specific to fecal pollution.…”
mentioning
confidence: 99%
“…Wilson, Twigg, Wright, Hendry, Cowell & Mair, 1935; Clegg & Sherwood, 1939; Sherwood & Clegg, 1942; Batty-Smith, 1942; Allen, Brooks & Williams, 1949), have found ability to ferment bile salts lactose broth a t 44" a reasonably specific test for Bacterium coli type I, and a method of enumeration based on this test was outlined by the Ministry of Health (1939). Disadvantages of the method are the large quantity of medium required and the large error involved in the computation of the most probable number.…”
mentioning
confidence: 99%
“…for the primary isolation and detection of organisms of fecal origin. Sherwood and Clegg (6,7) contended that the most reliable test for the detection of "Bacterium coli" was incubation in Mac-Conkey's broth at 44°C. Experimental results obtained with pure cultures of organisms from shellfish, sewage and feces were offered in support of their argument.…”
mentioning
confidence: 99%